ОТЛИЧИЕ ДИСТРИБЬЮТОРСКОГО ДОГОВОРА ОТ ДИЛЕРСКОГО ДОГОВОРА - АРСЕНИ, Игорь (SUPREMANCE OF LAW, 2016)
In the article the author reveals the peculiarities of separate contracts - a distributor and dealer. Separately, it is concluded that the data contract in legal science is often identified, but the study proved and identified the main distinguishing features of the contractual structures of data that allowed us to exclude all previously existing contradictions on the subject.